2010
DOI: 10.2174/1874120701007010001
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endothelial Cells in Myocardial Ischemia-Reperfusion Injury

Abstract: Minimizing myocardial ischemia-reperfusion injury has broad clinical implications and is a critical mediator of cardiac surgical outcomes. “Ischemic injury” results from a restriction in blood supply leading to a mismatch between oxygen supply and demand of a sufficient intensity and/or duration that leads to cell necrosis, whereas ischemia-reperfusion injury occurs when blood supply is restored after a period of ischemia and is usually associated with apoptosis (i.e. programmed cell death). Compared to vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 159 publications
1
82
1
1
Order By: Relevance
“…These findings and ours taken together suggest that hyperinsulinemia, plays a key role in the paradoxical protective effect of obesity in ischemia/ reperfusion injury through modulation of the RISK signaling. Insulin resistance may cause endothelial dysfunction and, therefore, influence myocardial susceptibility to reperfusion injury [21]. However, our present data do not show changes in endothelial-dependent vascular relaxation in response to 6 months of HFD feeding and, a recent ex vivo study using a mice model with vascular insulin resistance and vascular dysfunction, showed that insulin can directly activate myocardial PI3K/ Akt and protect against reperfusion injury despite the absence of functional insulin receptors in the endothelium [43].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…These findings and ours taken together suggest that hyperinsulinemia, plays a key role in the paradoxical protective effect of obesity in ischemia/ reperfusion injury through modulation of the RISK signaling. Insulin resistance may cause endothelial dysfunction and, therefore, influence myocardial susceptibility to reperfusion injury [21]. However, our present data do not show changes in endothelial-dependent vascular relaxation in response to 6 months of HFD feeding and, a recent ex vivo study using a mice model with vascular insulin resistance and vascular dysfunction, showed that insulin can directly activate myocardial PI3K/ Akt and protect against reperfusion injury despite the absence of functional insulin receptors in the endothelium [43].…”
Section: Discussioncontrasting
confidence: 88%
“…It is generally accepted that reduction of reperfusion injury is associated with the activation of the RISK pathway components [18], including Akt, which is also a key enzyme in the insulin signaling pathway [19]. However, obesity with insulin resistance is characterized by endothelial dysfunction [20], and may negatively influence myocardial susceptibility to reperfusion injury [21].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a capillary is next to almost every CM, and the distance between these 2 types of cells are very short (approximately 1-2 mm). 3,6 CMECs not only constitute the most important part of the microcirculation by supplying nutrition and oxygen but also possess unique CM-protective functions through HIF-a/ eNOS activation and neuregulin secretion during myocardial reperfusion injury. 4,35 Our study focused on the preservation of CMECs, or microcirculation protection in vitro, rather than CM protection itself.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that endothelial cells are more vulnerable to reperfusion injury but that CMs are more sensitive to ischemic injury. 6,7 However, the protection of endothelial cells against reperfusion injury has received much less attention than CMs or the myocardium, as indicated by PubMed searches ("myocardial" or "cardiomyocyte" and "reperfusion injury," 14,207 articles vs. "cardiac" and "endothelial" and "reperfusion injury," 759 articles).…”
Section: Introductionmentioning
confidence: 99%
“…As a basic component of the myocardial microcirculation, CMECs have a critical role in the protection of cardiomyocytes against MIRI [3]. Although CMECs are more sensitive to the reperfusion injury than cardiomyocytes [4], endothelial cells (ECs) have received considerably less attention in relation to reperfusion injury. To date, few studies have been published to clarify the proteins in CMECs in MIRI and to describe the functions and interactions of the altered proteins.…”
Section: Introductionmentioning
confidence: 99%